IMPLIKASI HUKUM DAN PENEGAKAN HUKUM DALAM MEMPERSIAPKAN BONUS DEMOGRAFI DI INDONESIA - Evan Katana; Taun Taun (Civilia: Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2023)
Indonesia is predicted to experience demographic bonuses in 2030-2040. By the time Indonesia is experiencing demographic bonuses, the proportion of the population of productive age (15-64 years) will be greater if compared to the non-productive age (65 years and over) with a share of more than 60% of the total population of Indonesia by 2030-2040 of 297 million people. Demographic bonus in Indonesia is one of the opportunities to make Indonesia an advanced country in accordance with the ideals of the Indonesian people who want to be advanced countries. But when these demographic bonuses are not prepared and used properly, they can create problems that will occur in the future if not in the face of now. The attitude that the government should take in embracing the demographic bonus in Indonesia is to expand the absorption of labour by opening up jobs so that the problem of unemployment can be addressed by opening jobs. The government must take policy by formulating laws and implementing good law enforcement so that it can attract a lot of investment from abroad and domestically. Legal roles in attracting foreign or domestic investment such as providing legal certainty, reducing licensing barriers, intensive enforcement of entrepreneurs, development of education and employment training programmes, provision of legal support for enterprise, and protection of investors in conducting economic activities in Indonesia. This is what the government can do as a policymaker and enforcer in preparing itself to take advantage of the demographic bonus that will occur in Indonesia.